1997
DOI: 10.1038/sj.bmt.1700975
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy and peripheral blood stem cell infusion in patients with non-Hodgkin’s lymphoma: results of outpatient treatment in community cancer centers

Abstract: Summary:Keywords: high-dose chemotherapy; non-Hodgkin's lymphoma; autologous stem cells The outcomes for patients with non-Hodgkin's lymphoma (NHL) treated with high-dose chemotherapy (HDC) and peripheral blood stem cell (PBSC) infusion by practicing oncologists in community cancer centersPatients with recurrent or refractory non-Hodgkin's lymin the United States were determined. Eighty-three phoma (NHL) may respond to further conventional treatpatients with NHL, who had failed conventional chemoment but few a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…On the other hand, the 3-5 year EFS achieved with chemotherapy-only regimens for the treatment of patients with lymphoma have ranged between 46% and 35%. [9][10][11][12] Although patients in our study had less favorable characteristics, the outcome of patients treated with highdose Bu/Mel/T regimen at the FHCRC is comparable to both the TBI-based and chemotherapy-only regimens reported in other trials. We did have somewhat more toxicity than would be expected from other regimens in the early phases of the trial.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, the 3-5 year EFS achieved with chemotherapy-only regimens for the treatment of patients with lymphoma have ranged between 46% and 35%. [9][10][11][12] Although patients in our study had less favorable characteristics, the outcome of patients treated with highdose Bu/Mel/T regimen at the FHCRC is comparable to both the TBI-based and chemotherapy-only regimens reported in other trials. We did have somewhat more toxicity than would be expected from other regimens in the early phases of the trial.…”
Section: Discussionmentioning
confidence: 59%
“…2 Radiation-based and chemotherapy-only preparative regimens have been evaluated in patients with NHL. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, the superiority of a specific HDC conditioning regimen for NHL has not been proven and few comparisons between regimens have been reported. [12][13][14][15] The Fred Hutchinson Cancer Research Center (FHCRC) has evaluated both radiation-based and chemotherapy-only conditioning regimens for the treatment of lymphomas.…”
mentioning
confidence: 99%
“…The only comparison data for these costs to caregivers are from the National Hospice Study, an evaluation of the costs and quality of care for terminally ill cancer patients. 5 This study demonstrated that 60% of caregivers reported a loss of income because of care-related time missed from work, averaging $2582. The median cost to caregivers in our study was Bone Marrow Transplantation similar to the cost of caregiving in the hospice setting and in Jagannath's outpatient stem cell transplant study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies including this report have demonstrated the safety of this approach and significant cost-savings, particularly among standard risk patients. [2][3][4][5][6][7][8][9] Whereas the majority of prior studies have measured direct medical costs, we also studied indirect costs to the caregiver including lost 'opportunity costs' and out-of-pocket expenses. At our institution, outpatient transplantation was associated with approximately $14 000 in savings in direct medical costs, without any decrement in quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation